Fueling Organized Crime: The Mexican War on Drugs and Oil Thefts - Giacomo Battiston; Gianmarco Daniele; Marco Le Moglie; Paolo Pinotti (Center for Economic Studies and ifo Institute (CESifo), 2022)
We show that the War on Drugs launched by the Mexican President Felipe Calderón in 2007 pushed drug cartels into large-scale oil thefts. Municipalities that the presidential candidate's party barely won at the local elections in 2007-2009 exhibit a larger increase in illegal oil taps over the following years, compared to municipalities in which the presidential candidate's party barely lost the elections. Challenger cartels in the drug market leapfrog incumbent drug cartels when entering the new illegal activity, analogous to what is typically observed in legal markets. Since challengers and incumbents specialize in different criminal sectors, the expansion of challengers does not increase violence in municipalities traversed by oil pipelines. At the same time, the municipalities traversed by a pipeline witness a decrease in schooling rates.
Keywords: K42; L20; 330; organized crime; War on Drugs; oil thefts; leapfrogging